Antibody Prevalence and Risk Factors for Toxoplasma gondii Infection in Women from Multan, Pakistan. (9th January 2017) - Nazir, M. M.; Akhtar, M.; Maqbool, A.; Waheed, A.; Sajid, M. A.; Ali, M. A.; Oneeb, M.; Alam, M. A.; Ahmad, A. N.; Nazir, N.; Fatima, S.; Lindsay, D. S.
Summary: Toxoplasma gondii infections are prevalent in humans and warm‐blooded animals. Maternal infections during pregnancy may have devastating consequences for transplacentally infected neonates. This study was conducted to examine the seroprevalence of antibodies to T. gondii in pregnant women of childbearing age and determine risk factors associated with pregnancy history, pet ownership, social and cultural factors at Nishtar Hospital, Multan. Samples were collected from 403 women and examined using a commercially available enzyme‐linked immunosorbent assay (ELISA). The overall prevalence of antibodies to T. gondii was 17.6% (71) in the 403 samples collected from women. Antibodies to T. gondii were present in 19.4% (45) of 232 pregnant women and 15.2% (26) of the samples from 171 non‐pregnant women. This study identified miscarriage history, pet ownership, type of residence, marital status, source of drinking water and eating habits as significant ( P < 0.05) risk factors associated with the presence of antibodies to T. gondii infection. Seroprevalence was not significantly different ( P > 0.05 ) in women from different ethnic groups based upon lifestyle and culture.